Investigating the Association between Flowering Time and Defense in the Arabidopsis thaliana-Fusarium oxysporum Interaction - Lyons, Rebecca (PLoS One, 2015)
Plants respond to pathogens either by investing more resources into immunity which is costly to development, or by accelerating reproductive processes such as flowering time to ensure reproduction occurs before the plant succumbs to disease. In this study we explored the link between flowering time and pathogen defense using the interaction between Arabidopsis thaliana and the root infecting fungal pathogen Fusarium oxysporum. We report that F. oxysporum infection accelerates flowering time and regulates transcription of a number of floral integrator genes, including FLOWERING LOCUS C (FLC), FLOWERING LOCUS T (FT) and GIGANTEA (GI). Furthermore, we observed a positive correlation between late flowering and resistance to F. oxysporum in A. thaliana natural ecotypes. Late-flowering gi and autonomous pathway mutants also exhibited enhanced resistance to F. oxysporum, supporting the association between flowering time and defense. However, epistasis analysis showed that accelerating flowering time by deletion of FLC in fve-3 or fpa-7 mutants did not alter disease resistance, suggesting that the effect of autonomous pathway on disease resistance occurs independently from flowering time. Indeed, RNA-seq analyses suggest that fve-3 mediated resistance to F. oxysporum is most likely a result of altered defense-associated gene transcription. Together, our results indicate that the association between flowering time and pathogen defense is complex and can involve both pleiotropic and direct effects.